Politika ironije na spletnih družbenih omrežjih - Slukan, Nejc (Teorija in praksa, 2021)
The article aims to give the theoretical foundations upon which we can analyse ironic communication practices in social media. Special emphasis is paid to trolling practices. Irony is understood in the article not just as a rhetorical figure, but as a speech act that reconfigures the relationships between the elements of the communicative situation. We first critically summarise contemporary versions of the theory of technological affordances before proceeding to conceptualise, by describing the conditions of communication in certain social media, some of their affordances as part of a dispositive, which we tentatively call the media-trolling dispositive and which encourages individuals to express themselves by way of trolling. We conclude that the affordances of social media encourage troll-like forms of expression
Keywords: čustva; dispozitiv; Družbeni mediji; emotions; ironija; irony; neoliberalism; neoliberalizem; online social media; Online social networks; political discourse; politični diskurz; Social media; social media networks; Spletna družabna omrežja; spletna družbena omrežja; trolanje; trolling; zmožnosti